First Quality Tissue Plant, Lock Haven, Pennsylvania: A Case Study Of Drilled Displacement Dewaal Piles ? Introduction - Gordon King (Deep Foundations Institute, 2004)
The site of the First Quality Tissue plant is located on a previous paper production facility in Lock Haven, Pennsylvania. The new development, which included the construction of a tissue machine building, baled building, converting building, various storage buildings and an electrical switchgear building, required the use of deep foundation systems to transfer loads below compressible fill and alluvial soils. Loading details provided by Jacobs Engineering, the project structural engineer, detailed braced steel frame buildings with typical column loads ranging from 75 to 150 kips and slab live loads of 250 to 300 psf. As an exception to this, however, the tissue machine and stock preparation building, which had a roof height ranging up to 85 feet, had column loads ranging up to 800 kips in addition to high dynamic loads. The First Tissue plant is located in a river valley in the hills of Western Pennsylvania. To evaluate the proposed site conditions and to formulate recommendations for the structure foundations, a geotechnical study was performed by the owner. Approximately 30 borings were advanced to bedrock, with wire-line coring performed in the tissue machine building. The borings disclosed a soil profile comprising of the following: